2021
DOI: 10.1177/15353702211000310
|View full text |Cite
|
Sign up to set email alerts
|

Sounding out the hidden data: A concise review of deep learning in photoacoustic imaging

Abstract: The rapidly evolving field of photoacoustic tomography utilizes endogenous chromophores to extract both functional and structural information from deep within tissues. It is this power to perform precise quantitative measurements in vivo—with endogenous or exogenous contrast —that makes photoacoustic tomography highly promising for clinical translation in functional brain imaging, early cancer detection, real-time surgical guidance, and the visualization of dynamic drug responses. Considering photoacoustic tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…PAM technology has seen improvement in imaging speed, field-of-view, resolution, and sensitivity ( Wang et al, 2021 ). These improvements have come from the application of novel high-speed multi-spectra light sources ( Cho et al, 2018 , 2021 ; Chen et al, 2022 ), deep learning imaging enhancement ( DiSpirito et al, 2020 , DiSpirito et al, 2021 ), innovative scanning configurations ( Liu and Yao, 2018 ), and exogenous contrast agents ( Borg and Rochford, 2018 ). These developments have allowed for better quantification and visualization of the hemodynamics of ischemic stroke.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…PAM technology has seen improvement in imaging speed, field-of-view, resolution, and sensitivity ( Wang et al, 2021 ). These improvements have come from the application of novel high-speed multi-spectra light sources ( Cho et al, 2018 , 2021 ; Chen et al, 2022 ), deep learning imaging enhancement ( DiSpirito et al, 2020 , DiSpirito et al, 2021 ), innovative scanning configurations ( Liu and Yao, 2018 ), and exogenous contrast agents ( Borg and Rochford, 2018 ). These developments have allowed for better quantification and visualization of the hemodynamics of ischemic stroke.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Limited by space, we will focus on several important developments that have overcome the longstanding limits in traditional PAT. Interested readers are referred to comprehensive review articles that provide in-depth analyses and discussions on low-cost light sources, 22 , 26 28 novel ultrasound sensors, 21 , 29 , 30 PA contrast agents, 29 , 31 , 32 PA endoscopy, 33 , 34 deep learning enhanced PAT, 35 37 as well as clinical translation of PAT. 22 , 38 41 …”
Section: Technical Advances In Patmentioning
confidence: 99%
“…Specifically in the realm of machine learning strategies, many deep-learning network models are being investigated to improve PA image reconstruction methodologies [20][21][22][23]. Several important studies, including recent reviews [24][25][26][27] in deep learning with laser-based systems, addressed the problem of under-sampled data sparsity due to the limited number of detectors. While many studies demonstrated the results on numerically simulated data and in vitro phantoms [28][29][30][31][32][33][34][35], only a handful of studies tested their deep-learning models on in vivo data.…”
Section: Introductionmentioning
confidence: 99%